2021
DOI: 10.1098/rsob.200408
|View full text |Cite
|
Sign up to set email alerts
|

The tumour suppressor brain tumour (Brat) regulates linker histone dBigH1 expression in the Drosophila female germline and the early embryo

Abstract: Linker histones H1 are essential chromatin components that exist as multiple developmentally regulated variants. In metazoans, specific H1s are expressed during germline development in a tightly regulated manner. However, the mechanisms governing their stage-dependent expression are poorly understood. Here, we address this question in Drosophila , which encodes for a single germline-specific dBigH1 linker histone. We show that during female germline lineage differentiation, dBigH1 is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…BigH1 is expressed in both male and female germlines with similar expression patterns [ 50 , 65 , 66 ]. While the function in the female germline is not known, in males, BigH1 is important for germ stem cell maintenance and spermatocyte differentiation [ 65 ].…”
Section: Chromatin Composition and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…BigH1 is expressed in both male and female germlines with similar expression patterns [ 50 , 65 , 66 ]. While the function in the female germline is not known, in males, BigH1 is important for germ stem cell maintenance and spermatocyte differentiation [ 65 ].…”
Section: Chromatin Composition and Structurementioning
confidence: 99%
“…BigH1 is retained in precellular embryos, where it is important in maintaining the silencing of the zygotic genome [ 50 ]. Recent studies have focused on the different properties of the two linker histones and have found that BigH1 has a greater repression ability than the somatic H1 due to its higher content in acidic residues [ 66 ]. Moreover, nucleosomes containing BigH1 are more stable, but show higher mobility than H1-nucleosomes [ 67 ].…”
Section: Chromatin Composition and Structurementioning
confidence: 99%
“…Germline-enriched histone H1 variants have been reported in many metazoan species, and studies on the model species of some key taxa have revealed that the germline-enriched H1 variants play crucial roles in gametogenesis ( Pérez-Montero et al, 2016 ). In insects, one of the most diverse groups of animals on Earth, the knowledge of germline-enriched H1 variants was limited to Drosophila species ( Carbonell et al, 2017 ; Climent-Cantó et al, 2021 ), and very little is known about these variants in other insects. In this study, we reported two testis-specific highly expressed H1 variant genes ( PpH1V1 and PpH1V2 ) in the parasitoid wasp P. puparum , and functional studies suggested that PpH1V1 is associated with male fertility in the wasp.…”
Section: Discussionmentioning
confidence: 99%
“…Mediates polarity to ensure a robust pattern of asymmetric division [163] Tumor suppressor brain tumor (Brat) Regulates the linker histone dBigH1 expression [164] Niche-derived Hh and Wnts and germline-derived EGFs Promotes the differentiation of GSCs [165] Insulin/IGF signaling, TOR signaling, and GCN2-dependent amino acid sensing Promotes the proliferation and maintenance of the stem/progenitor population [161,162] Retinoic acid-STRA8 signaling…”
Section: Female Drosophilamentioning
confidence: 99%